Solitary parotid metastasis 8 years after a nephrectomy for renal cell carcinoma - Hussain, Faiz (J Community Hosp Intern Med Perspect, 2016)
Renal cell carcinoma is a common cancer, known for its aggressive behavior and ability to metastasize nearly every organ system in the body. While the cancer commonly spreads to a select few organs and metastasis usually develops within 5 years of diagnosis, there have been numerous case reports of atypical sites of metastasis and cases of relapse up to decades after treatment. We present a case a 65-year-old male who presented with right preauricular swelling 8 years after the initial diagnosis and right nephrectomy for clear cell renal cell cancer. We take a look at previous case reports with similar presentations.